Magnesium Technology 2015 2015
DOI: 10.1007/978-3-319-48185-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Solute Segregation and Aggregation in Mg Alloys

Abstract: Extended AbstractThe addition of adequate amounts of rare-earth (RE) alloying elements can produce appreciable effects on microstructures, formability and mechanical properties of magnesium alloys. At low concentrations, it can weaken the basal texture in the asdeformed and the recrystallized conditions in wrought alloys and improve the creep resistance of casting alloys at elevated temperatures; at high concentrations, it can bring significant age hardening effects and thus improve the alloy strength. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…It can lead to the occurrence of static strain aging (SSA) and dynamic strain aging (DSA) [6,7] depending on the deformation conditions. Besides, researchers also found that RE atoms trend to segregate at grain boundaries and have a great influence on the dynamic recrystallization (DRX) behavior of magnesium alloys [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to the occurrence of static strain aging (SSA) and dynamic strain aging (DSA) [6,7] depending on the deformation conditions. Besides, researchers also found that RE atoms trend to segregate at grain boundaries and have a great influence on the dynamic recrystallization (DRX) behavior of magnesium alloys [8][9][10].…”
Section: Introductionmentioning
confidence: 99%